Assessment of traffic load events and structural effects on road bridges based on strain measurements - Sousa, Helder; Costa, Bruno J. A.; Henriques, António Abel; Bento, João; Figueiras, Joaquim A. (Journal of Civil Engineering and Management, 2016)
Several technical and scientific publications have been made available focussing on Bridge Weight-in-Motion (BWIM) concerning railway bridges. On the contrary, BWIM analysis on road bridges are more scarce and therefore, this work intends to provide a contribution by presenting the BWIM analysis performed on two major road bridges in Portugal – Lezíria Bridge and Pinhão Bridge. These bridges are equipped with electric and optical strain gauges, acquisition systems with features that allow high sampling rates. Based on the collected data and focussing on the bridges’ lifetime, a probabilistic approach to quantify extreme traffic loads was implemented using extreme distribution functions. The bridges’ behaviour to these extreme traffic loads is numerically evaluated and a comparison with the alarm levels established by the bridge designers is performed. Although the bridge’s safety is not compromised, it was concluded that the representativeness of the observation period is a critical issue and the analysis of this kind of results must be carefully considered. A comprehensive discussion about this matter is carried out at the end of this work.First published online: 13 Dec 2015